Problem loans : a banker's guide - Checkley, Keith; Dickinson, Keith (London : Euromoney Books, 2000)
Analyzes and discusses international distressed debt and the developing standards of practice and documentation which accompany the different trading platforms worldwide.
Commissioned by Euromoney.
Includes bibliographical references.
oif 17/02/17
Loans
Keywords: Commercial loans; Risk management; Bank loans